Core-shell, wire-in-tube and nanotube structures: Carbon-based materials by molecular layer deposition for efficient microwave absorption. (March 2021) - Yan, Lili; Li, Lanlan; Ru, Xiaoxia; Wen, Danning; Ding, Lei; Zhang, Xueyun; Diao, Haipeng; Qin, Yong
Abstract: The absorption of electromagnetic waves by materials is usually realized by multiple mechanisms, such as interface polarization, defect polarization, multiple reflections and scattering, conductive loss and magnetic loss. Therefore, attributing microwave absorption (MA) to specific mechanisms without separating them through effective means is not rigorous. Herein, three different structures: ZnO–C core-shell nanowires, ZnO–C wire-in-tubes and carbon nanotubes, were prepared through the molecular layer deposition of polyimide on ZnO nanowires and subsequent calcination at specific temperatures. Results show that the hollow structure is beneficial to MA performance. The reflection loss (RL) values of wire-in-tube and nanotube structures are much higher than the RL values of the core-shell structure. The RL peak of nanotube structure can reach −64.42 dB. Then again, multicomponent modulation is conducive to impedance matching resulting in board effective absorption bandwidth (EAB). The EAB of the wire-in-tube structure with two components is wider than that of the nanotube structure with one component, reaching as wide as 5.76 GHz. The results substantiate the effect of hollow structure and composition on the MA performance, providing a strong basis for the design and optimization of MA materials. Graphical abstract: Image 1 Highlights: The structures were controlled by adjusting calcination temperature. Microwave absorption performance of the three structures were investigated and compared. The microwave response mechanism is discussed in depth.